Penyuluhan Pencegahan Demam Dengue dan Pelatihan Juru Pemantau Jentik (Jumantik) di Desa Seri Kembang III Ogan Ilir - Ahmad Ghiffari; Gumar Herudiansyah; Gusmiatun Gusmiatun; Helwan Kasra; Sulton Nawawi; Amira Azza Nabila; Sinta Nabila (Abdimas Universal, 2024)
Cases of Dengue Fever (DF) increased in Seri Kembang III Village, and a child died with three childreen hospitalized at the Regional Hospital in Ogan Ilir Regency. The government increase awareness by increasing public knowledge and skills by collaborating with academia. Students of the Universitas Muhammadiyah Palembang (UMP) Community Service Program (KKN) collaborated with Faculty of Medicine UMP to performed counseling activities and training for larva monitoring (Jumantik). Activities include counseling and evaluating the level of community knowledge through pretest and posttest. The training includes skills to identify mosquito larvae, which was followed by checking the homes of people affected. by DD to educate and find out the breeding habitat for Aedes aegypti mosquito larvae in the environment around residential areas. The participants' knowledge showed an increase regarding the symptoms, causes, prevention and role of jumantik as seen from the development of the pretest posttest results which increased significantly and the enthusiasm shown by the participants in the question and answer session with the resource person. It is hoped that activities like this can be carried out again by KKN students to provide education to local village residents and help residents increase awareness of the transmission of dengue fever (DHF).